Correlation between electronic micro-roughness and surface topography in two-dimensional surface conducting hydrogen-terminated diamond - Yianni, Steve A.; Creedon, Daniel L.; Schenk, Alex K.; Xing, Kaijian; Akhgar, Golrokh; Hoxley, David I.; Ley, Lothar; McCallum, Jeffrey C.; Pakes, Christopher I. (Diamond and Related Materials, 2021)
The influence of surface topography on phase coherent transport in the two-dimensional (2D) hole band of surface transfer doped hydrogen-terminated (100) diamond is investigated. Low-temperature magneto-conductance measurements were carried out with an applied in-plane magnetic field to quantify the effect of electronic micro-roughness on spin dephasing in the 2D hole band for Hall bar devices with similar transport characteristics, but significantly different topographic roughness. The electronic micro-roughness of the 2D hole band, described by the parameter d2L, where d is the root-mean-square (rms) fluctuation in the width of the quantum well and L is the correlation length of the fluctuations, is found to increase for surfaces with increased roughness. Fluctuations in the well width likely arise from a locally varying hole carrier density, arising for example from a local variation in the concentration of ionic components in the surface water layer.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Diamond; Phase coherent backscattering; Weak anti-localisation; Weak localization